2003
DOI: 10.1002/macp.200390041
|View full text |Cite
|
Sign up to set email alerts
|

Polyacetylenes Bearing Mesogenic Side Groups: Synthesis and Properties, 2

Abstract: We report on the synthesis of novel liquid crystalline polyacetylenes derived from monosubstituted acetylene monomers. In the monomers A1OBP‐Acn obtained from 3‐bromo‐1‐propyne, the acetylenic moiety is linked through a very short spacer to a biphenyl mesogenic core. Several linear acyl groups of different length are introduced as tail groups. Most of the monomers show liquid crystalline behavior. Polymerizations are carried out in solution with typical metathesis catalysts based on Mo and W and yield polyacet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…Following the general synthetic methods [4,5], we synthesized the monosubstituted polyacetylene PHBOP. After purification and drying in a vacuum oven, PHBOP in the form of powders were obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the general synthetic methods [4,5], we synthesized the monosubstituted polyacetylene PHBOP. After purification and drying in a vacuum oven, PHBOP in the form of powders were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…For examples, Davey et al [1] and Whitehead et al [2] investigated the polarized photoluminescence (PL) from liquid crystalline polymers. Recently, several research groups synthesized a novel class of side-chain liquid crystalline polyacetylenes by introducing orientable mesogenic pendant onto the rigid backbone of polyacetylene [3][4][5][6]. Their optical characterization has demonstrated that the dilute solutions of these side-chain liquid crystalline polyacetylenes can give off efficient deep-blue or blue PL [5][6][7][8][9][10] although the pristine polyacetylenes can give off weak PL only in the infrared region [11].…”
Section: Introductionmentioning
confidence: 99%
“…Years ago, we observed intense deep-blue emissions from a class of mono-substituted polyacetylenes with biphenyl side-chains, and our results have demonstrated that the biphenyl pendants are responsible for the deep-blue emissions of those mono-substituted polyacetylenes [4][5][6][7]. Recently, Stagnaro et al [8] observed blue emission from polyacetylenes bearing biphenyl mesogens to the backbone via short methylene spacers; they suggested that both the polymer backbone and the biphenyl chromophore in the side group play a role in the blue emission. Due to the complexity in the photo-physics of conjugated polymers [9], it is clear that the origin of the blue emissions is still open to question for the polyacetylenes with side chains.…”
Section: Introductionmentioning
confidence: 90%
“…As mentioned above, Hsu and co-workers find that the cis-rich polymers without spacer do not show LC behavior. However, in the study of the influence of short flexible spacer, [80][81][82] Costa and coworkers found that, with only a single methylene spacer, the SCLCPAs can form Sm phases. Such a short spacer cannot decouple the dynamics of main and side-chains.…”
Section: Sheet-like Mspas and Their Smectic Lc Phasesmentioning
confidence: 99%